Influence of Old Age on Risk of Lymph Node Metastasis and Survival in Patients With T1 Colorectal Cancer: A Population-Based Analysis - Ye, Hua; Zheng, Bin; Zheng, Qi; Chen, Ping (Frontiers in Oncology, 2021)
Background We aimed at determining the influence of old age on lymph node metastasis (LNM) and prognosis in T1 colorectal cancer (CRC). Methods We collected data from eligible patients in Surveillance, Epidemiology, and End Results database between 2004 and 2015. Independent predictors of LNM were identified by the logistic regression analysis. Cox regression analysis, propensity score-matched analysis and competing risks analysis were used to analyze the associations between old age and lymph node (LN) status, and to validate the prognostic value of old age on cancer-specific survival (CSS). Results In total, 10092 patients were identified. Among them, 6423 patients (63.6%) had greater than or equal to 12 examined lymph nodes (LNs) (LNE >=12), and 5777 patients (57.7%) were of 65 years or older. The observed rate of LNM was 4.6% (15 out of 325) in T1 CRC elderly patients that tumor size<3cm, well differentiated, negative CEA level and adenocarcinoma.Logistic regression models demonstrated that tumor size 3cm (odds ratio, OR = 1.316, P = 0.038), poorly differentiated (OR = 3.716, P <0.001), older age (OR = 0.633 for age 65–79 years, OR= 0.477 for age over 80 years, both P < 0.001), and negative CEA level (OR = 0.71, P =0.007) were independent prognostic factors. Cox regression analysis demonstrated CSS was not significantly different between elderly patients undergoing radical resection with LNE12 and those with LNE <12 (HR= 0.865, P = 0.153), which were firmly validated after propensity score-matched analysis by a competing risks model. Conclusions The predictive value of tumor size, grading, primary site, histology, CEA level and age for LNM should be considered in medical decision making about local resection. We found that tumor size<3cm, well differentiated, negative CEA level and adenocarcinoma in elderly patients with T1 colorectal cancer who were suitable for Local excision.